GENERAL CRITICISM ASSESSMENT OF ISLAMIC BANKING AND FINANCE - Kamaruddin Kamaruddin; Silvana Dwi Novianty; M. Shabri A. Majid; Marliyah Marliyah; Rita Handayani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Islamic banking and finance has shown impressive growth in the world over the past three decades. This achievement has come a long way, most of the financial services having interest-based banking and non-bank financial institutions have provided shari’a system. However, in some financial sectors at national and global levels are still very low in implementing the shari’a system. The main factors behind this phenomenon are the existence of a number of myths and a lot of confusion about Islamic finance theory among the public and intellectuals. So there are also misunderstandings about Islamic banking and criticisms about its theory and practice have been discussed directly or indirectly in various places, both in discussions, writings and even in books on this subject. The system that emerged was subject to a number of myths and harsh criticism, not only by those who did not accept the prohibition of interest but also by "devout" people both lay and learned who visualized the ideal system without giving any weight to the challenges of evolution and the problems of teething and difficulty. Islamic finance concepts and philosophies are based on sound reasons and are accepted by an increasing number of people around the world. What practitioners need to do is create awareness so that it can dispel myths among the public. Regarding the practice of Islamic banking, it is necessary to implement strict internal controls to avoid systemic and operational risks.